2012
DOI: 10.1152/ajpheart.00256.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gene deletion of P2Y4 receptor lowers exercise capacity and reduces myocardial hypertrophy with swimming exercise

Abstract: Nucleotides released within the heart under pathological conditions can be involved in cardioprotection or cardiac fibrosis through the activation purinergic P2Y(2) and P2Y(6) receptors, respectively. We previously demonstrated that adult P2Y(4)-null mice display a microcardia phenotype related to a cardiac angiogenic defect. To evaluate the functional consequences of this defect, we performed here a combination of cardiac monitoring and exercise tests. We investigated the exercise capacity of P2Y(4) wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…P2Y 4 , described as a UTP receptor (16), displays a very restricted tissue distribution including heart and lung, and its physiological role has been poorly investigated. We have previously demonstrated that adult P2Y 4 -null mice display a microcardia phenotype related to a cardiac angiogenic defect (23) and a reduced exercise tolerance (24). The present study identifies a protection against myocardial infarction in P2Y 4 -null mice.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…P2Y 4 , described as a UTP receptor (16), displays a very restricted tissue distribution including heart and lung, and its physiological role has been poorly investigated. We have previously demonstrated that adult P2Y 4 -null mice display a microcardia phenotype related to a cardiac angiogenic defect (23) and a reduced exercise tolerance (24). The present study identifies a protection against myocardial infarction in P2Y 4 -null mice.…”
Section: Discussionsupporting
confidence: 62%
“…P2Y 4 -null mice have been generated in our laboratory (22) and we demonstrated P2Y 4 (23). We showed recently that this receptor is involved in postnatal heart development (23), as well as in exercise tolerance and exercise-induced cardiac hypertrophy (24).…”
mentioning
confidence: 81%
“…Overexpression of human P2X4R in ventricular myocytes of a transgenic mouse increased basal cardiac contractility without cardiac hypertrophy or failure [274] and activation with a P2X4R agonist had beneficial effects [483]. Deletion of the P2Y4R gene in mice lowered exercise capacity and reduced myocardial hypertrophy [737].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…Cardioprotective effect of UTP has been previously described: treatment with UTP prior to myocardial infarction leads to reduced ischemic damage through P2Y 2 receptor activation (1,2). Another UTP receptor, P2Y 4 , plays an important role in the heart: P2Y 4 knock-out (KO) mice display reduced cardiac angiogenesis and cardiac postnatal development (3), as well as lower exercise capacity and reduced exercise-induced cardiac hypertrophy (4). More recently, it has been shown that P2Y 4 KO mice display lower infarct size and reduced cardiac inflammation and fibrosis in a model of ligation of the left anterior descending artery (5).…”
mentioning
confidence: 96%
“…Another UTP receptor, P2Y 4 , plays an important role in the heart: P2Y 4 knock-out (KO) mice display reduced cardiac angiogenesis and cardiac postnatal development (3), as well as lower exercise capacity and reduced exercise-induced cardiac hypertrophy (4). More recently, it has been shown that P2Y 4 KO mice display lower infarct size and reduced cardiac inflammation and fibrosis in a model of ligation of the left anterior descending artery (5). The study of the role of P2Y 6 UDP receptor in the heart has also been initiated.…”
mentioning
confidence: 99%